South American tectonics: An introduction. (November 2018) - Oliveros, Verónica; Folguera, Andrés; Arriagada, César; De Fátima Bitencourt, María
Highlights: This volume gathers articles at the 1st Symposium on South American Tectonics (Atecsud).